Surgical revision of radial head fractures: a multicenter retrospective analysis of 466 cases - Hackl, Michael; Wegmann, Kilian; Hollinger, Boris; El-Zayat, Bilal F.; Seybold, Dominik; Gühring, Thorsten; Schnetzke, Marc; Schmidt-Horlohé, Kay; Greiner, Stefan; Lill, Helmut; Ellwein, Alexander; Glanzmann, Michael C.; et al. (Journal of shoulder and elbow surgery, 2019)
Background - Radial head fractures lead to persisting disability in a considerable number of cases. This study aimed to investigate their most common revision causes and procedures. - Methods - This multicenter retrospective study reviewed the cases of 466 adult patients who had undergone surgical revision after operative or nonoperative treatment of a radial head fracture. The initial diagnosis was a Mason type I fracture in 13.0%, Mason type II fracture in 14.6%, Mason type III fracture in 22.8%, Mason type IV fracture in 20.9%, terrible-triad injury in 12.8%, Monteggia-like lesion in 13.1%, and Essex-Lopresti lesion in 2.0%. Initial treatment was nonoperative in 30.2%, open reduction and internal fixation (ORIF) in 44.9%, radial head arthroplasty in 16.6%, radial head resection in 3.7%, sole treatment of concomitant injuries in 2.6%, and fragment excision in 2.0%. Up to 3 revision causes and procedures were recorded per case. - Results - The most common complications were stiffness (67.4%), instability (36.5%), painful osteoarthritis (29.2%), ORIF related (14.8%), nonunion or necrosis (9.2%), radial head arthroplasty related (7.5%), ulnar neuropathy (6.0%), and infection (2.6%). Revision procedures frequently included arthrolysis (42.1%), arthroplasty (24.9%), implant removal (23.6%), ligament repair or reconstruction (23.0%), débridement (14.2%), repeated ORIF (8.2%), and/or radial head resection (7.7%). Mason type I or II fractures were primarily revised because of stiffness and painful osteoarthritis. Complications after Mason type III fractures were predominantly ORIF related. Fracture-dislocations showed a wide range of complications, with instability and stiffness comprising the most common causes of revision. - Conclusions - The complications of radial head fractures are characteristic to their classification. Knowledge of these findings might guide surgeons in treating these injuries and may help counsel patients accordingly.